The role of entrepreneurial architecture in achieving the dimensions of sustainable quality (An exploratory study of the opinions of a sample of administrative leaders in private hospitals in Dohuk Governorate / Iraq) - Khaleel Ghazi, Sazan; Ibrahim Ameen Hussien, Hanar; Rasheed Soltan, Hikmat (Academic Journal of Nawroz University, 2023)
The current research seeks to diagnose the role of entrepreneurial architecture in achieving the dimensions of sustainable quality, an exploratory study of the views of administrative leaders in private hospitals in Dohuk Governorate, as the researchers built a hypothetical model, benefiting from the theoretical literature on the subject, Which takes the correlation and influence relationships between the dimensions of entrepreneurial architecture as an independent variable and sustainable quality as a dependent variable. The researchers adopted the questionnaire as a tool for collecting data from the research sample (84) from the administrative leaders in the private hospitals in Dohuk Governorate. The researchers used a number of statistical methods to ensure the validity of the research hypotheses, all of which were subjected to multiple statistical tests. And The research reached a number of theoretical conclusions, most notably that the entrepreneurial architecture supports all the goals of the organization and its development, being a coherent set of principles and methods to achieve the dimensions of sustainable quality of health service, which is an important factor in creating high satisfaction among the beneficiaries dealing with the surveyed hospitals. Among the most important practical conclusions that have been reached is that improving the levels of entrepreneurial architecture will lead to improving sustainable quality levels in the surveyed hospitals. The research concluded with a set of proposals, the most important of which is the achievement of high levels of quality and its sustainability. It is related to the researched hospitals working on rehabilitating their medical and administrative cadres skillfully, by participating in training courses outside the region, and this is reinforced by acquiring knowledge from those with experience globally and regionally.